Atypical patterns of tone production in tone-language-speaking children with autism - Xu, Kunyu; Yan, Jinting; Ma, Chenlu; Chang, Xuhui; Chien, Yu-Fu (Frontiers in Psychology, 2022)
Speakers with autism spectrum disorders (ASD) are found to exhibit atypical pitch patterns in speech production. However, little is known about the production of lexical tones (T1, T2, T3, T4) as well as neutral tones (T1N, T2N, T3N, T4N) by tone-language speakers with ASD. Thus, this study investigated the height and shape of tones produced by Mandarin-speaking children with ASD and their age-matched typically developing (TD) peers. A pronunciation experiment was conducted in which the participants were asked to produce reduplicated nouns. The findings from the acoustic analyses showed that although ASD children generally produced both lexical tones and neutral tones with distinct tonal contours, there were significant differences between the ASD and TD groups for tone height and shape for T1/T1N, T3/T3N, and T4/T4N. However, we did not find any difference in T2/T2N. These data implied that the atypical acoustic pattern in the ASD group could be partially due to the suppression of the F0 range. Moreover, we found that ASD children tended to produce more errors for T2/T2N, T3/T3N than for T1/T1N, T4/T4N. The pattern of tone errors could be explained by the acquisition principle of pitch, similarities among different tones, and tone sandhi. We thus concluded that deficits in pitch processing could be responsible for the atypical tone pattern of ASD children, and speculated that the atypical tonal contours might also be due to imitation deficits. The present findings may eventually help enhance the comprehensive understanding of the representation of atypical pitch patterns in ASD across languages.